5x-2-(-3x+4)=

Simple and best practice solution for 5x-2-(-3x+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-2-(-3x+4)= equation:


Simplifying
5x + -2 + -1(-3x + 4) = 0

Reorder the terms:
5x + -2 + -1(4 + -3x) = 0
5x + -2 + (4 * -1 + -3x * -1) = 0
5x + -2 + (-4 + 3x) = 0

Reorder the terms:
-2 + -4 + 5x + 3x = 0

Combine like terms: -2 + -4 = -6
-6 + 5x + 3x = 0

Combine like terms: 5x + 3x = 8x
-6 + 8x = 0

Solving
-6 + 8x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 8x = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 8x = 0 + 6
8x = 0 + 6

Combine like terms: 0 + 6 = 6
8x = 6

Divide each side by '8'.
x = 0.75

Simplifying
x = 0.75

See similar equations:

| 6r-9=7+4r | | 5x+7-3(2x+9)=2(x-8)-13 | | 2m+1*5= | | 4(2x+4)-20=12 | | 2(a-8)=10 | | r-ll/3=-7 | | -3(5t-4)+5t=7t-7 | | 2w+4-(3w+6)= | | -75=3g | | 20=-5/3z | | 3p*1/3=114 | | (u-10)*6=48 | | 3*1/3p=114 | | x*log(x)=600000000 | | -2.4n-3+(7.8n+2)= | | Y=-1/2x-12 | | -.5(8x-6)=6x-7 | | 10+6+3x=7*3.5 | | -2m(1+4m)5=-13 | | 2(2l-3+l)=36 | | -(3/x)=0 | | 13/6-1/2 | | 10+4+3x=7*3.5 | | 24.5=2.5-4c | | 7+7y=12x-56 | | -(3/x)0 | | 7v^2+224=-84v | | 10x+20y=360 | | a(n-5)+6=bn | | 6q+1+(q+11)= | | 16+3x=7*3.5 | | 30-45=18 |

Equations solver categories